Cuestiones sobre el "Chronicon Mundi" de Lucas de Tuy (4,32: "infra"; 4, 35: "Gundissaluus sanctionis", "Portella de Arenis"; 4, 36: "uallem Prauiarensem"; 4,37: "Vallis Cesar") - Martínez Ortega, Ricardo (2012)
Estudio crítico, filológico e histórico de las voces infra, Gundissaluus sanctionis, Portella de Arenis, uallem Prauiarensem y Vallis Cesar en la última edición filológica del Chronicon Mundi de Lucas de Tuy a través de la historiografía y documentación medieval latina y española.
A critical, philological and historical study of the words infra, Gundissaluus sanctionis, Portella de Arenis, uallem Prauiarensem and Vallis Cesar, in the last philological edition of Lucas de Tuy’s Chronicon Mundi, trough the historiography and the medieval Latin and Spanish documentation.
Keywords: Lucas de Tuy, -- m. 1249; Toponimia; Lengua española; Filología latina; Crítica textual